Sameuramide A, a new cyclic depsipeptide isolated from an ascidian of the family Didemnidae. Issue 13 (30th July 2018) - Machida, Koshi; Arai, Daisuke; Katsumata, Ryosuke; Otsuka, Satoshi; Yamashita, Jun K.; Ye, Tao; Tang, Shoubin; Fusetani, Nobuhiro; Nakao, Yoichi
Graphical abstract: Highlights: A new cyclic depsipeptide isolated from an ascidian of the family Didemnidae. Maintained colony formation of murine embryonic stem cells without LIF. Activated potential multipotency of embryoid bodies. Abstract: Sameuramide A (1 ), a new cyclic depsipeptide encompassing one each of alanine, N -methyl alanine, N -methyl dehydroalanine, N, O -dimethyl threonine, phenyllactic acid, three β -hydroxy leucines, and two propionates, was isolated from a didemnid ascidian collected at the northern part of Japan. The planar structure was established based on the interpretation of MS and NMR data. The absolute configuration of the subunits was determined by the advanced Marfey's method and the chiral LC-MS analysis. Compound1 exhibited the activity of maintaining colony formation of murine embryonic stem (mES) cells without leukemia inhibitory factor (LIF). Down regulation of the gene expression of Krüppel-like transcription factor 4 ( Klf4 ) indicated that1 itself was not able to maintain the undifferentiated state of the mES cells. However, the expression levels of the marker genes ( Nestin, T, Sox17 ) for three germ layers were upregulated in embryoid bodies (EBs) after treatment of1 together with LIF, suggesting that1 plays a supportive role for LIF in maintaining the multipotency of mES cells.